(untitled) (American Journal of Economics and Business Innovation, 2025)
The increasing trends of transparency, accountability, and sustainability have placed Environmental, Social and Governance (ESG) reporting at the centre of the global financial markets. Nevertheless, the swift proliferation of ESG frameworks has shown that it has serious issues, such as uneven metrics, a lack of cross-regional comparability, and the concern of greenwashing. New opportunities of Big Data analytics are emerging in the area of improving ESG reporting through real-time monitoring, predictive insights, and data-driven transparency. This paper discusses how Big Data has transformed ESG reporting in the financial sector and specifically how the emerging technologies can help to transform disclosures to become more credible, standardized, and investor-relevant. The article based on the recent literature examines how financial institutions utilize the Big Data tools, including artificial intelligence, blockchain, and natural language processing, to enhance ESG measurement, risk management, and sustainable investment decisions. Both developed and developing market case studies are taken into account to illustrate the practical implications of the Big Data-powered ESG practices. The results imply that the inclusion of Big Data into ESG reporting raises the level of credibility, helps in streamlining portfolios, and establishes a relationship between financial markets and long-term sustainability objectives. However, the paper also points to current obstacles, including barriers to data integration, high costs to implement and ethical issues in algorithmic decision-making. The research finds that, although Big Data provides a route to more effective ESG reporting, its effectiveness still requires more effective regulatory frameworks, cross-industry cooperation, and adoption of the technology, especially in emerging economies. The study becomes part of the emerging literature on sustainable finance and will serve as a basis on which policymakers, investors, and financial institutions can ensure profitability and sustainability are consistent with each other.